1998
DOI: 10.1152/physrev.1998.78.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Signaling in the Development and Modification of Synapses

Abstract: Retrograde signaling from the postsynaptic cell to the presynaptic neuron is essential for the development, maintenance, and activity-dependent modification of synaptic connections. This review covers various forms of retrograde interactions at developing and mature synapses. First, we discuss evidence for early retrograde inductive events during synaptogenesis and how maturation of presynaptic structure and function is affected by signals from the postsynaptic cell. Second, we review the evidence that retrogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
130
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(139 citation statements)
references
References 366 publications
9
130
0
Order By: Relevance
“…This involves changes in the number of vesicles in presynaptic terminals, and changes in the composition of the exocytosis machinery and the postsynaptic receptor complex [9,43,44] (Figure 1). The studies on purified RGCs Glia enhance the number of synapses per neuron, as estimated by three different experimental approaches: FM1-43 labeling of active terminals (using data from Ref.…”
Section: Astrocytes Control Synapse Numbermentioning
confidence: 99%
“…This involves changes in the number of vesicles in presynaptic terminals, and changes in the composition of the exocytosis machinery and the postsynaptic receptor complex [9,43,44] (Figure 1). The studies on purified RGCs Glia enhance the number of synapses per neuron, as estimated by three different experimental approaches: FM1-43 labeling of active terminals (using data from Ref.…”
Section: Astrocytes Control Synapse Numbermentioning
confidence: 99%
“…Retrograde signals also flow across the synapse on a slower timescale to regulate the development, maintenance and modification of the properties of the presynaptic neuron 1,[37][38][39][40][41] . Gradual loss of synapses at the dendrites after axotomy [42][43][44] or interruption of axonal transport 45 has demonstrated the existence of slow axon-dendritic trophic interaction of the order of days to weeks which is crucial for maintaining the structural and functional integrity of synaptic inputs at the dendrites.…”
Section: Information Flow In a Neural Networkmentioning
confidence: 99%
“…There are two general categories of retrograde signaling that differ in their time courses and modes of action (Fitzsimonds and Poo, 1998;Ginty and Segal, 2002). One type is primarily trophic and involves long-distance transport of target-derived signals from distal terminals to the nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…For these types of synaptic plasticity, it is known that action potential firing can evoke BDNF release (Balkowiec and Katz, 2000;Hartmann et al, 2001), but it is not known whether moderate depolarization, of the type observed early during development (Ben-Ari, 2002), is also capable of inducing BDNF release. Moreover, it has not been fully shown whether BDNF actually fulfills the conditions necessary to qualify as a retrograde signaling molecule (Fitzsimonds and Poo, 1998), particularly at the single-cell level (Alger, 2002). To establish this point, the test criteria include the following: (1) induction of postsynaptic release from a single cell; (2) demonstration that the postsynaptic release elicits a change in presynaptic activity; and (3) confirmation that BDNF is the diffusible messenger by exogenous application, block with specific antagonists and scavengers, and inhibition of release.…”
Section: Introductionmentioning
confidence: 99%